2006
DOI: 10.1128/aem.00668-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Highly Hop-ResistantLactobacillus brevisStrain Lacking Hop Transport

Abstract: Resistance to hops is a prerequisite for lactic acid bacteria to spoil beer. In this study we analyzed mechanisms of hop resistance of Lactobacillus brevis at the metabolism, membrane physiology, and cell wall composition levels. The beer-spoiling organism L. brevis TMW 1.465 was adapted to high concentrations of hop compounds and compared to a nonadapted strain. Upon adaptation to hops the metabolism changed to minimize ethanol stress. Fructose was used predominantly as a carbon source by the nonadapted strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 53 publications
5
62
0
2
Order By: Relevance
“…Nonetheless these membrane-bound defense mechanisms are inevitably energy-consuming, and malate, citrate, pyruvate and arginine were identified as energy sources for ATP production in beer, where most nutrients are depleted by brewing yeast 108 . As for energy-independent defense systems, lipoteichoic acids located in the cell wall were reported to provide a reservoir of divalent cations, which are otherwise scarce as a result of complexation with hop bitter acids 11,12,134 . The ratio of 16:0 fatty acid content to 16:1 fatty acid content, which is considered important in proton ionophore resistance, was also reported to increase substantially upon hop adaptation of beer spoilage LAB 11 .…”
Section: Hop Resistance Of Beer Spoilage Labmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless these membrane-bound defense mechanisms are inevitably energy-consuming, and malate, citrate, pyruvate and arginine were identified as energy sources for ATP production in beer, where most nutrients are depleted by brewing yeast 108 . As for energy-independent defense systems, lipoteichoic acids located in the cell wall were reported to provide a reservoir of divalent cations, which are otherwise scarce as a result of complexation with hop bitter acids 11,12,134 . The ratio of 16:0 fatty acid content to 16:1 fatty acid content, which is considered important in proton ionophore resistance, was also reported to increase substantially upon hop adaptation of beer spoilage LAB 11 .…”
Section: Hop Resistance Of Beer Spoilage Labmentioning
confidence: 99%
“…As for energy-independent defense systems, lipoteichoic acids located in the cell wall were reported to provide a reservoir of divalent cations, which are otherwise scarce as a result of complexation with hop bitter acids 11,12,134 . The ratio of 16:0 fatty acid content to 16:1 fatty acid content, which is considered important in proton ionophore resistance, was also reported to increase substantially upon hop adaptation of beer spoilage LAB 11 . The morphological studies further showed that beer spoilage LAB occur in beer as shorter rods (Fig.…”
Section: Hop Resistance Of Beer Spoilage Labmentioning
confidence: 99%
See 2 more Smart Citations
“…They exert bacteriostatic effects on most Gram-positive bacteria as they act as proton ionophores and dissipate the transmembrane pH gradient. Several LAB species, such as Lactobacillus spp., have been found to have acquired beer-spoilage ability due to hop resistance genes (horA and horC), and consideration must be given to the fact that altering the hop composition of beer can have a profound impact on the organoleptic and physico-chemical properties of the final product 6,21,22,33,35 .…”
Section: Introductionmentioning
confidence: 99%